Pengaruh Life Cycle Perusahaan Terhadap Tax Avoidance Pada Emiten Bei Periode 2017-2019 - Mely Sutanto; Permata Ayu Widyasari (Universitas Katolik Soegijapranata, Semarang, 2022)
The study aims to prove the relationship between the firm's life cycle stages and tax avoidance. This study uses Dickinson (2011) model as the proxy of the life cycle stages, which based on cash flow patterns. The sample in this study are 195 companies engaged in the manufacturing sector that listed on the Indonesia Stock Exchange (IDX). The results of regression model shows that firm life cycle stages have a significant determinant on the tendency of companies do tax avoidance. This study is expected to be useful for management, investors, and academics as a guide to make a better decision.